Correlation of troponin-I level with left ventricular systolic dysfunction after first attack of non-ST segment elevation myocardial infarction - Khan, Mahmood H.; Islam, Mirza Md. Nazrul; Islam, Md. Shafiqul; Khan, Kaisar Nasrullah; Chowdhury, Shamim; Rahman, Reazur (International Journal of Research in Medical Sciences, 2019)
Background: Coronary Heart Disease (CHD) is the most common category of the heart disease and is found to be the single most important cause that leads to premature death in the developed world. Recognizing a patient with ACS is important because the diagnosis triggers both triage and management. cTnI is 100% tissue-specific for the myocardium and it has shown itself as a very sensitive and specific marker for AMI. Ventricular function is the best predictor of death after an ACS. It serves as a marker of myocardial damage and provides information on systolic function as well as diagnosis and prognosis. The study aimed at investigating the impact of LVEF on elevated troponin-I level in patients with first attack of NSTEMI. Methods: This cross-sectional analytical study was conducted in the department of cardiology in Mymensingh Medical College Hospital from December, 2015 to November, 2016. Total 130 first attack of NSTEMI patients were included considering inclusion and exclusion criteria. The sample population was divided into two groups: Group-I: Patients with first attack of NSTEMI with LVEF: ≥55%. Group-II: Patients with first attack of NSTEMI with LVEF: <55%. Then LVEF and troponin-I levels were correlated using Pearson’s correlation coefficient test. Results: In this study mean troponin-I of group-I and group-II were 5.53±7.43 and 16.46±15.79ng/ml respectively. It was statistically significant (p<0.05). The mean LVEF value of groups were 65.31±10.30% and 40.17±4.62% respectively. It was statistically significant (p<0.05). The echocardiography showed that patients with high troponin-I level had low LVEF and patients with low troponin-I level had preserved LVEF. Analysis showed that patients with highest level of troponin-I had severe left ventricular systolic dysfunction (LVEF <35%) and vice versa-the patients with the lowest levels of troponin-I had preserved systolic function (LVEF ≥55%). In our study, it also showed that the levels of troponin-I had negative correlation with LVEF levels with medium strength of association (r= -0.5394, p=0.001). Our study also discovered that Troponin-I level ≥6.6ng/ml is a very sensitive and specific marker for LV systolic dysfunction. Conclusions: The study has enabled the research team to conclude that the higher is the Troponin-I level the lower is the LVEF level and thus more severe is the LV systolic dysfunction in first attack of NSTEMI patients.